New regulations on compounds, film-forming materials, and film-forming methods.

JP2026166714APending Publication Date: 2026-10-14TRI CHEM LAB
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2025059853
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

Smart Images

  • Figure 2026166714000001_ABST
    Figure 2026166714000001_ABST
Patent Text Reader

Abstract

The objective is to provide a technology that enables the formation of a Co-containing film that is highly stable in terms of heat retention, easy to transport to the deposition chamber, and capable of forming a high-quality (e.g., low-resistance) and conformable Co-containing film. [Solution] A novel compound represented by Co[tBu-NC(R)N-nPr]2 (where R is a hydrocarbon group).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a novel Co-containing organic compound, a film-forming material (precursor) for forming, for example, a Co-containing film, and a film-forming method for forming, for example, a Co-containing film.

Background Art

[0002] With the increase in speed of semiconductor devices and the miniaturization of wiring patterns, Cu, which has higher conductivity than Al and excellent electromigration resistance, has come to be used as wiring. Electroplating is used for forming such a Cu wiring film. For example, first, a Cu seed layer is deposited (coated) on the flat portions of trenches (such as side walls and bottom portions) and the flat portions of vias (such as side walls) by PVD (Physical Vapor Deposition). Thereafter, Cu is embedded by electroplating. For fine wiring patterns around the 28 nm node, a Co thin film is deposited on a barrier metal such as TaN serving as an underlayer, in order to form a conformable coating of the Cu seed layer on the side walls of trenches and vias. The Co thin film improves wettability with Cu. In order to improve EM (Electromigration) reliability, a Co cap (a Co film is coated (formed) on the top surface of the Cu wiring) is provided. For fine wiring patterns around the 7 nm node, since Cu embedding by electroplating is difficult, the adoption of Co for the wiring film itself has been investigated.

[0003] For example, Surface and Coatings Technology (Volume 258, Part A, 25 November 2014, Pages 98-101) discloses a method of forming a Co-containing film by PEALD (Plasma-Enhanced Atomic Layer Deposition) using CCTBA as a raw material. The aforementioned CCTBA is a Co material containing carbonyl groups (CO). Since Co acts as a catalyst for CO dissociation, there is a risk that a large amount of carbon (C) may be mixed into the Co-containing film during deposition.

[0004] The Japanese Journal of Applied Physics (Volume 46, L173) discloses a method for forming a Co-containing film using CpCo(CO)2 and Co2(CO)8 as raw materials and PEALD. The aforementioned CpCo(CO)2 and Co2(CO)8 are Co materials containing CO. Since Co acts as a catalyst for CO dissociation, there is a risk that a large amount of carbon (C) may be mixed into the Co-containing film during deposition. Furthermore, because CpCo(CO)2 has a high thermal decomposition temperature, there is a risk that a large amount of carbon (C) may be mixed into the Co-containing film during deposition.

[0005] For the reasons mentioned above, Co materials that do not contain CO in their molecules have been investigated. In particular, Co materials containing amidinate groups have attracted attention. Japanese Patent No. 5225957 discloses a Co-containing film formed by CVD (Chemical Vapor Deposition) film formation technology. In this patent, cobalt amidinate [Co(tBu-Et-Et-amd)2] is used as a precursor. Japanese Patent Publication No. 2011-063849 discloses a Co-containing film formed by CVD (Chemical Vapor Deposition) technology. In this invention, cobalt amidinate [Co(tBu-Et-Et-amd)2] is used as a precursor. Japanese Patent No. 4988159 discloses a Co-containing film formed using ALD (Atomic Layer Deposition) film deposition technology. In this patent, cobalt amidinate [Co(iPr-AMD)2,Co(iBu-AMD)2] is used as a precursor. Japanese Patent No. 7332211 discloses a Co-containing film based on CVD film deposition technology. In this patent, cobalt amidinates [bis(N,N'-diisopropylbutaneamidinate)cobalt, bis(N,N'-diisopropyl-2-methylpropionamidinate)cobalt] are used. [Prior art documents] [Patent Documents]

[0006] [Patent Document 1] JP5225957B [Patent Document 2] JP2011-63849A [Patent Document 3] JP4988159B [Patent Document 4] JP7332211B [Non-patent literature]

[0007] [Non-Patent Document 1] Surface and Coatings Technology Volume 258, Part A, 25 November 2014, Pages 98-101 [Non-Patent Document 2] Japanese Journal of Applied Physics,Volume 46, L173 [Overview of the project] [Problems that the invention aims to solve]

[0008] In this field, the Co materials (precursors: Co metal-organic compounds) proposed so far have not always been sufficient. For example, because Co had a high affinity for C, N, and O, high-quality, conformable Co-containing films had not been obtained. For example, the Co precursor was in a solid state at 25°C (1 atmosphere). Therefore, it was necessary to heat or maintain the temperature of the transport pipes. Without heating or temperature maintenance, the precursor would adhere to and accumulate on the inner walls of the transport pipes during the transport process, blocking the pipes and hindering transport. This made transport difficult during the transport process (the process of transporting the Co precursor to the Co-containing film deposition process). In particular, in large-scale factories, heating and temperature maintenance requires large-scale equipment, resulting in high costs.

[0009] Therefore, the problem that the present invention aims to solve is to provide a novel Co material (precursor: Co metal-organic compound) that can solve the aforementioned problems. For example, when forming a Co-containing film by CVD and / or ALD, the invention aims to provide a technology that can form a Co-containing film that is highly stable for storage, easy to transport to the deposition chamber, and of high quality (e.g., low resistance) and conformable. [Means for solving the problem]

[0010] The present invention We propose a novel compound [represented by Co[tBu-NC(R)N-nPr]2 (where R is a hydrocarbon group)].

[0011] The present invention proposes a novel compound in which the compound is preferably a liquid (at 25°C (1 atm)).

[0012] The present invention proposes a novel compound in which the number of carbon atoms in R of the aforementioned compound is preferably 1 to 4.

[0013] The present invention proposes a novel compound in which R of the aforementioned compound is preferably an alkyl group.

[0014] The present invention proposes a novel compound in which R of the aforementioned compound is preferably selected from the group of Me, Et, Pr, and Bu. The present invention proposes a novel compound in which R of the aforementioned compound is preferably Me.

[0015] The present invention A material used for forming a Co-containing film, wherein the material is a compound represented by Co[tBu-NC(R)N-nPr]2 (R is a hydrocarbon group) is proposed as a film-forming material.

[0016] The present invention proposes the film-forming material, wherein the compound is preferably a liquid (at 25°C under 1 atm).

[0017] The present invention proposes the film-forming material, wherein the number of carbon atoms in R of the compound is preferably 1 to 4.

[0018] The present invention proposes the film-forming material, wherein R of the compound is preferably an alkyl group. The present invention proposes the film-forming material, wherein R of the compound is preferably any one selected from the group consisting of Me, Et, Pr and Bu. The present invention proposes the film-forming material, wherein R of the compound is preferably Me.

[0019] The present invention proposes the film-forming material, which preferably further comprises a reducing agent in addition to the compound represented by Co[tBu-NC(R)N-nPr]2 (R is a hydrocarbon group).

[0020] The present invention proposes the film-forming material, wherein the reducing agent is preferably any one selected from the group consisting of ammonia and hydrogen. The present invention proposes the film-forming material, wherein the reducing agent is preferably ammonia and hydrogen.

[0021] The present invention relates to a method for forming a Co-containing film, wherein the compound represented by Co[tBu-NC(R)N-nPr]2 (R is a hydrocarbon group) is supplied into a film formation chamber, and the film is formed on a substrate inside the film formation chamber is proposed as a film formation method.

[0022] The present invention proposes the method for forming a Co-containing film, wherein the compound is preferably a liquid (at 25°C under 1 atm).

[0023] The present invention proposes a method for forming the aforementioned Co-containing film, wherein the number of carbon atoms in R of the compound is preferably 1 to 4.

[0024] The present invention proposes a method for forming the aforementioned Co-containing film, wherein R in the compound is preferably an alkyl group. The present invention proposes a method for forming the aforementioned Co-containing film, wherein R in the compound is preferably selected from the group consisting of Me, Et, Pr, and Bu. The present invention proposes a method for forming a Co-containing film, wherein R in the compound is preferably Me.

[0025] The present invention proposes a method for forming a Co-containing film, wherein, in addition to the compound represented by Co[tBu-NC(R)N-nPr]2 (where R is a hydrocarbon group), a reducing agent is preferably supplied. The present invention proposes a method for forming a Co-containing film, wherein, in addition to the compound represented by Co[tBu-NC(R)N-nPr]2 (where R is a hydrocarbon group), a reducing agent is preferably supplied to the film formation chamber.

[0026] The present invention proposes a film formation method in which the reducing agent is preferably selected from the group consisting of ammonia and hydrogen. The present invention proposes a film formation method in which the reducing agent is preferably ammonia and hydrogen. [Effects of the Invention]

[0027] Since a compound represented as Co[tBu-NC(R)N-nPr]2 (where R is a hydrocarbon group) was used, a high-quality Co-containing film (e.g., volumetric efficiency of 18.5 μΩcm) was obtained at a relatively low deposition temperature (e.g., 250°C). [Brief explanation of the drawing]

[0028] [Figure 1][Compound 1:Co[tBu-NC(Me)N-nPr]2] TG diagram [Figure 2] TG diagram of [Compound 2: Co[iPr-NC(nPr)N-iPr]2] [Figure 3] Vapor pressure curves of compound 1 and compound 2 [Figure 4] Schematic diagram of film deposition apparatus [Figure 5] Comparison diagram of volume resistivity of compound 1 and compound 2 [Modes for carrying out the invention]

[0029] The following detailed description provides only preferred exemplary embodiments and is not intended to limit the scope, applicability, or configuration of the invention. Rather, it provides to those skilled in the art an explanation for carrying out / enabling preferred exemplary embodiments of the invention. Various modifications can be made to the function and arrangement of the elements without departing from the spirit and scope of the invention as set forth in the appended claims.

[0030] The first aspect of the present invention is a novel compound. The compound is represented as [Co[tBu-NC(R)N-nPr]2 (where R is a hydrocarbon group)]. The compound was, for example, a liquid (at 25°C (1 atm)). The number of carbon atoms in R was, for example, 1 to 4. The R in the compound was, for example, an alkyl group. Preferably, it was one selected from the group of Me (methyl group), Et (ethyl group), Pr (propyl group: propyl group without a side chain (nPr), or propyl group with a side chain (iPr)), Bu (butyl group: butyl group without a side chain (nBu), or butyl group with a side chain). Examples of alkyl groups having a branched chain (side chain) include iPr (iso-propyl group: -CH(CH3)2), iBu (iso-butyl group), sBu (sec-butyl group), and tBu (tert-butyl group: -C(CH3)3). Particularly preferred was Me.

[0031] The second aspect of the present invention is a film-forming material. The film-forming material is a material used for forming a Co-containing film. The material is a compound represented as Co[tBu-NC(R)N-nPr]2 (where R is a hydrocarbon group). In this specification, "the film-forming material is a compound" may mean "the film-forming material contains (has) a compound." The compound (Co[tBu-NC(R)N-nPr]2) was, for example, a liquid (at 25°C (1 atm)). The number of carbon atoms in R was, for example, 1 to 4. The R in the compound was, for example, an alkyl group. Preferably, it was one selected from the group of Me (methyl group), Et (ethyl group), Pr (propyl group: propyl group without a side chain, or propyl group with a side chain), Bu (butyl group: butyl group without a side chain, or butyl group with a side chain). Examples of alkyl groups having branched chains (side chains) include iPr (iso-propyl group: -CH(CH3)2), iBu (iso-butyl group), sBu (sec-butyl group), and tBu (tert-butyl group: -C(CH3)3). Me was particularly preferred. In addition to the compound represented by Co[tBu-NC(R)N-nPr]2 (where R is a hydrocarbon group), the material preferably contains a reducing agent. The reducing agent may be any reducing agent, but preferably it was selected from the group consisting of ammonia and hydrogen. More preferably it was ammonia and hydrogen.

[0032] The third aspect of the present invention is a film deposition method. The film deposition method is a method for forming a Co-containing film. In the method, a compound represented by Co[tBu-NC(R)N-nPr]2 (where R is a hydrocarbon group) is supplied into a film deposition chamber. The supplied compound is deposited on a substrate in the film deposition chamber. As a result, a Co-containing film is formed on the substrate. The compound was, for example, a liquid (at 25°C (1 atm)). In the field of metal-containing film deposition, a liquid precursor is preferable to a solid precursor. For example, in the process of transporting a solid precursor to the metal-containing film deposition process, the solid precursor may adhere to and deposit on the inner wall surface of the transport pipe. This may cause the transport pipe to become blocked. To prevent this problem, the transport pipe needs to be heated and kept warm. Heating and keeping warm is costly. Moreover, even with warming, there are minute spaces between the solid precursors. As a result, the heat transferred to the solid precursors becomes uneven. Therefore, there remains a risk that the solid precursor may adhere to and accumulate on the inner wall surface of the transport pipe. For this reason, it is preferable that the precursor be in liquid form during the transport process. The number of carbon atoms in R was, for example, 1 to 4. In the compound, R was, for example, an alkyl group. Preferably, it was one selected from the group of Me (methyl group), Et (ethyl group), Pr (propyl group: propyl group without a side chain (nPr), or propyl group with a side chain (iPr)), Bu (butyl group: butyl group without a side chain (nBu), or butyl group with a side chain). Examples of alkyl groups having a branched chain (side chain) include iPr (iso-propyl group: -CH(CH3)2), iBu (iso-butyl group), sBu (sec-butyl group), and tBu (tert-butyl group: -C(CH3)3). Particularly preferred was Me. In addition to the compound represented by Co[tBu-NC(R)N-nPr]2 (where R is a hydrocarbon group), a reducing agent is preferably used. The reducing agent is supplied into the film deposition chamber. The reducing agent may be any reducing agent, but preferably it was selected from the group consisting of ammonia and hydrogen. More preferably, ammonia and hydrogen were used in combination.

[0033] The aforementioned compound (Co organic compound) is sometimes described as a complex. Because it is suitably used in CVD and ALD, it is also sometimes described as a precursor. Regardless of the notation, it should be considered to refer to the same substance.

[0034] ALD is used for film deposition. CVD can also be used. The aforementioned ALD is not limited to ALD in the narrow sense, but also includes ALD in the broad sense and similar ALDs. Similarly, the aforementioned CVD is not limited to CVD in the narrow sense, but also includes CVD in the broad sense and similar CVDs. For example, this includes pulsed CVD, laser CVD, cyclic CVD (CCVD), metal-organic CVD (MOCVD), plasma-enhanced CVD (PECVD), high-density PECVD, photon-assisted CVD, plasma-photon-assisted CVD (PPECVD), thermochemical vapor deposition, low-temperature chemical vapor deposition, chemically assisted vapor deposition, hot filament chemical vapor deposition, CVD of liquid polymer precursors, deposition from supercritical fluids and low-energy CVD (LECVD), plasma-enhanced ALD (PEALD), etc. In addition, CVD and ALDs employing radiation (X-rays, electron beams, electromagnetic waves, or light) are also included.

[0035] In the field of metal-containing film deposition, the deposition temperature (substrate temperature) is a crucial factor. Higher deposition temperatures promote faster film growth rates. However, higher deposition temperatures can cause decomposition of the deposition material, leading to the inclusion of impurities in the deposited metal-containing film. Decomposition of the deposition material allows chemical reactions to proceed continuously, resulting in film growth without self-regulation of the reaction. Higher deposition temperatures also lead to thermal damage to the substrate (substrate or base material) used for depositing the metal-containing film. Lower deposition temperatures minimize these disadvantages. In other words, lowering the deposition temperature offers significant advantages in the process of depositing metal-containing films. However, even at relatively low deposition temperatures, it cannot be said that impurities will not be incorporated into the deposited film. That is, while the risk of thermal decomposition of precursors is low, there is still a risk that undecomposed or / or unreacted precursors or products from within the deposition chamber (reaction chamber) (e.g., organic components generated during adsorption reactions to the substrate or products generated during reactions with reagents) may be incorporated into the deposited film. However, this risk cannot be ruled out in the case of high-temperature film deposition. Therefore, it would be preferable to use a lower deposition temperature. In other words, it would be preferable to be able to form a high-quality film at a lower temperature. When the novel compound was used, the film formation temperature was preferably 300°C or lower, more preferably 260°C or lower, preferably 100°C or higher, and even more preferably 150°C or higher. For example, it was 200°C or higher.

[0036] In general, in the field of metal-containing film deposition, a liquid precursor is preferable to a solid precursor. Liquid precursors can be transported more uniformly than solid precursors during the metal-containing film deposition process. A carrier gas is bubbled into the metal-containing film precursor under suitable process conditions. This bubbling is an effective means of increasing the contact time between the gas and the liquid. These actions aim to achieve a gas flow saturated with the vaporized precursor. Achieving a saturated carrier gas flow maximizes precursor transport and is advantageous in the operation of the metal-containing film deposition process. For film deposition, a carrier gas (e.g., N2) is supplied to the precursor, and the precursor is transported into the film deposition chamber by bubbling.

[0037] According to the present invention, the problems that the present invention aims to solve were solved. Film deposition was possible at a relatively low temperature (e.g., 250°C). High-quality Co-containing films (e.g., volumetric efficiency of 18.5 μΩcm) were obtained.

[0038] The present invention will be described in more detail below. The following description is merely a preferred exemplary embodiment and does not limit the present invention. Various modifications are also possible, without departing from the spirit and scope of the present invention as defined in the claims.

[0039] [Example 1] [Compound 1:Co[tBu-NC(Me)N-nPr]2] The synthesis was carried out under a nitrogen atmosphere. CoCl2 (5.0 g) and THF (50 ml) were added to a container. The container was cooled to -50°C to -78°C. A mixed solution of tBuN-NC(Me)N(H)-nPr (12.3 g) and nBuLi / nHexane (15 wt%: 34.3 g) was slowly added dropwise to the container. During this time, the container remained cooled to -50°C to -78°C. The mixture was stirred inside the container. After this, the cooling of the container was stopped. The temperature of the container gradually returned to room temperature. During this time, the mixture was stirred inside the container. After stirring at room temperature, the solvent of the resulting reaction mixture solution was removed by vacuum distillation. Extraction was carried out with n-Hexane (50 ml). The resulting reaction mixture was filtered. The solvent of the resulting reaction mixture was removed by vacuum distillation. The resulting crude product was purified by distillation. A dark green liquid was obtained.

[0040] The dark green compound was identified as Co[tBu-NC(Me)N-nPr]2 by NMR spectrometer (BRUKER AVANCEIII400).

[0041] The aforementioned compound was confirmed to have a weight loss rate of 98.88% and a weight loss rate of 50% (T50) of 218.9°C using a TG instrument (RIGAKU TG-TA 8122 / S) (see Figure 1). The aforementioned compound is found to have good volatility and good thermal stability. Therefore, it can be said that it is a suitable precursor for forming Co-containing films.

[0042] [Reference example 1] [Compound 2:Co[iPr-NC(nPr)N-iPr]2] Compound 2 was synthesized in accordance with Example 1, that is, by the same method as for Compound 1. The resulting crude product was purified by distillation. A dark green liquid was obtained.

[0043] The compound was identified as Co[iPr-NC(nPr)N-iPr]2 using AVANCEIII400.

[0044] The aforementioned compound was confirmed to have a weight loss rate of 98.54% and a T50 of 219.0°C using TG-DTA 8122 / S (see Figure 2). The aforementioned compound is found to have good volatility and good thermal stability. Therefore, it can be said that it is a suitable precursor for forming Co-containing films.

[0045] [Reference example 2] [Compound 3:Co[iPr-NC(Me)N-iPr]2] Compound 3 was synthesized in accordance with Example 1, that is, by the same method as for Compound 1. The resulting crude product was purified by distillation. A dark green liquid was obtained. This dark green liquid then transformed into a dark green solid.

[0046] The compound was identified as Co[iPr-NC(Me)N-iPr]2 using AVANCEIII400.

[0047] The aforementioned compound was confirmed to have a weight loss rate of 94.96% and a T50 of 198.6°C using TG-DTA 8122 / S. The aforementioned compound was found to have good thermal stability. However, it remained solid at 25°C (1 atm). Therefore, it is difficult to say that it is a suitable precursor for forming a Co-containing film.

[0048] [Reference example 3] [Compound 4:Co[iPr-NC(Et)N-iPr]2] Compound 4 was synthesized in accordance with Example 1, that is, by the same method as for Compound 1. The resulting crude product was purified by distillation. A dark green liquid was obtained. This dark green liquid then transformed into a dark green solid.

[0049] The compound was identified as Co[iPr-NC(Et)N-iPr]2 using AVANCEIII400.

[0050] The aforementioned compound was confirmed to have a weight loss rate of 90.41% and a T50 of 198.1°C using TG-DTA 8122 / S. The aforementioned compound was found to have good thermal stability. However, it remained solid at 25°C (1 atm). Therefore, it is difficult to say that it is a suitable precursor for forming a Co-containing film.

[0051] [Reference example 4] [Compound 5:Co[tBu-NC(Me)N-tBu]2] Compound 5 was synthesized in accordance with Example 1, that is, by the same method as for Compound 1. The resulting crude product was purified by distillation. A dark green liquid was obtained. This dark green liquid then transformed into a dark green solid.

[0052] The compound was identified as Co[tBu-NC(Me)N-tBu]2 using AVANCEIII400.

[0053] The aforementioned compound was confirmed to have a weight loss rate of 89.28% and a T50 of 217.9°C using TG-DTA 8122 / S. The aforementioned compound does not exhibit good volatility or good thermal stability. Moreover, it was a solid at 25°C (1 atm). Therefore, it is difficult to say that it is a suitable precursor for forming a Co-containing film.

[0054] [Reference example 5] [Compound 6:Co[tBu-NC(Et)N-tBu]2] Compound 6 was synthesized in accordance with Example 1, that is, by the same method as for Compound 1. The resulting crude product was purified by distillation. A dark green liquid was obtained. This dark green liquid then transformed into a dark green solid.

[0055] The compound was identified as Co[tBu-NC(Et)N-tBu]2 using AVANCEIII400.

[0056] The aforementioned compound was confirmed to have a weight loss rate of 74.56% and a T50 of 216.3°C using TG-DTA 8122 / S. The aforementioned compound does not exhibit good volatility or good thermal stability. Moreover, it was a solid at 25°C (1 atm). Therefore, it is difficult to say that it is a suitable precursor for forming a Co-containing film.

[0057] Table 1 shows the state of compounds 1-6 at 25°C (1 atm), the weight loss rate in TG, and T50. Table-1 Condition T50(℃) Weight reduction rate (%) Compound 1 Liquid 218.9 98.88 Compound 2 Liquid 219.0 98.54 Compound 3 Solid 198.6 94.96 Compound 4 Solid 198.1 90.41 Compound 5 Solid 217.9 89.28 Compound 6 Solid 216.3 74.56

[0058] The structure of compound 1 is as follows. JPEG2026166714000002.jpg46127

[0059] The structures of compounds 2 and 3 are as follows. JPEG2026166714000003.jpg46127

[0060] The vapor pressures of compounds 1 and 2 (measured by the static method) are shown in Table 2 and Figure 3. Table-2 Vapor pressure (60°C) Compound 1 0.207torr Compound 2 0.135torr

[0061] In the field of metal-containing film deposition, it is said that liquid precursors are preferable to solid precursors in the transport process for depositing the metal-containing film. From this perspective, compounds 1 and 2 can be said to be preferable precursors to compounds 3 and 4. The T50 temperature and weight loss rates in TG were similar for compound 1 and compound 2. Therefore, their physical properties regarding volatility and thermal stability were considered to be equivalent. However, as shown in Table 2 and Figure 3, the vapor pressure of compound 1 was far greater than that of compound 2. This was discovered for the first time through this invention. In the field of metal-containing film deposition, precursors with high vapor pressure are generally preferred over precursors with low vapor pressure. Therefore, in the field of metal-containing film deposition, compound 1 can be said to be a preferred precursor over compound 2.

[0062] [Example 2] [Formation of Co-containing film by ALD using compound 1] The apparatus shown in Figure 4 was used. The aforementioned compound 1[Co[tBu-NC(Me)N-nPr]2] was used as a precursor. A Co-containing film was deposited on an SiO2 substrate using ALD. The substrate placed in the film deposition chamber is heated to 150°C to 250°C. The precursor, placed in a stainless steel container, is heated to 85°C. N2 gas was supplied into the container at a flow rate of 100 sccm. Bubbling was performed. As a result, the precursor was supplied into the film deposition chamber. The precursor was supplied into the film deposition chamber for 5 seconds. Subsequently, NH3 gas and H2 gas were supplied for 0.1 seconds. Subsequently, N2 gas was supplied again for 5 seconds, causing bubbling. This supplied the precursor into the film deposition chamber. The above process was repeated 300 times. The above 300 steps were repeated to form a Co-containing film.

[0063] The film thickness of the aforementioned Co-containing film is shown in Table 3. A spectroscopic ellipsometer (HORIBA Jobin Yvon UVISELM200-FUV-FGMS) was used to measure the film thickness. The resistance values ​​of the aforementioned Co-containing film are shown in Table 3. The sheet resistance and volume resistivity are also shown in Table 3. The volume resistivity is also shown in Figure 5. A resistance meter (Mitsubishi Chemical Corporation Loresta-GP MCPT600) was used to measure the resistance. Table-3 Substrate temperature, film thickness, resistance value, sheet resistance value, volume resistivity (℃) (nm) (Ω) (Ω / □) (μΩcm) 200 24.713 184.4 767.5 1896.722 225 32.693 16.93 70.46 230.355 250 65.401 6.793 2.829 18.501

[0064] [Reference example 6] [Formation of Co-containing film by ALD using compound 2] Compound 2[Co[iPr-NC(nPr)N-iPr]2] was used as a precursor. A Co-containing film was formed on an SiO2 substrate in accordance with Example 2.

[0065] The film thickness of the aforementioned Co-containing film is shown in Table 4. A spectroscopic ellipsometer (HORIBA Jobin Yvon UVISELM200-FUV-FGMS) was used to measure the film thickness. The resistance values ​​of the aforementioned Co-containing film are shown in Table 4. The sheet resistance and volume resistivity are also shown in Table 3. The volume resistivity is also shown in Figure 5. A resistance meter (Mitsubishi Chemical Corporation Loresta-GP MCPT600) was used to measure the resistance. Table-4 Substrate temperature, film thickness, resistance value, sheet resistance value, volume resistivity (℃) (nm) (Ω) (Ω / □) (μΩcm) 175 15.84 97×10 4 4437×10 2 702820.8 250 42.392 24.99 102.8 435.790 300 42.844 11.79 44.89 192.326

[0066] Volumetric resistance (ρV) is the volumetric resistance value per unit volume of the test material. (V / I) × (S / L) V = Voltage applied to the test specimen I = Current value that flows when voltage is applied S = Cross-sectional area of ​​the test specimen L = Length of the test specimen The volume resistivity (Rv) is given by the formula (Rv = V / I). Therefore, ρV = Rv × (S / L). For test specimens of the same size (same S / L ratio), a higher volume resistivity results in a higher volume resistance, making it more difficult for electricity to flow. Conversely, a lower volume resistivity results in a lower volume resistance, making it easier for electricity to flow. The terminology for deposition resistivity varies depending on the field. For example, it is called electrical resistivity in the field of electrical engineering, resistivity in the field of physics, specific electrical resistance in the field of electronics, and volume resistivity in the field of materials science. Although the terminology differs from field to field, the meaning is the same. In semiconductor devices such as integrated circuits, multilayer wiring is used for transmitting electrical signals between elements and supplying power voltage. With the increase in integration density due to miniaturization, challenges in wiring technology are increasing, such as increased signal delay due to wiring and increased reliability problems. Wiring delay can be simply expressed as the product of wiring resistance (R) and wiring capacitance (C) (RC). To solve the problem of wiring delay, it is necessary to reduce wiring resistance. Materials with low wiring resistivity are desired. The aforementioned wiring resistivity can be rephrased as volume resistivity. To solve the problem of wiring delay, it can be rephrased as requiring materials with low volume resistivity. Compound 1 has a lower volume resistivity than Compound 2. This suggests that Compound 1 has lower wiring resistance. In other words, Compound 1 is a more preferable precursor than Compound 2 in the field of metal-containing film deposition (the field of semiconductors). This is something that has been discovered for the first time through this invention.

[0067] To illustrate the nature of the present invention, it will be understood that many further modifications, including details of materials, processes, and components, described and shown herein can be made by those skilled in the art within the principles and scope of the present invention as expressed in the appended claims. The present invention is not intended to be limited to the examples and / or embodiments described above.

Claims

1. A method for forming a Co-containing film, Co[tBu-NC(R)N-nPr] 2 A compound represented by (R is a hydrocarbon group) is supplied into the deposition chamber, and the film is formed on a substrate in the deposition chamber. Film formation method.

2. The compound is a liquid (at 25°C (1 atm)). The method for forming a film according to claim 1.

3. The R in the aforementioned compound is selected from the group consisting of Me, Et, Pr, and Bu. The method for forming a film according to claim 2.

4. The R in the aforementioned compound is Me. The method for forming a film according to claim 3.

5. In addition to the aforementioned compound, a reducing agent is supplied. Method 4 for film formation.

6. The reducing agent is ammonia and hydrogen. The method for forming a film according to claim 5.

7. The reducing agent is selected from ammonia and hydrogen. The method for forming a film according to claim 5.

8. The R is an alkyl group. The method for forming a film according to claim 1.

9. A material used for forming a Co-containing film, The aforementioned material is Co[tBu-NC(R)N-nPr] 2 A compound represented by (R is a hydrocarbon group). Thin-film deposition materials.

10. The compound is a liquid (at 25°C (1 atm)). The film-forming material according to claim 9.

11. The aforementioned R has 1 to 4 carbon atoms. The film-forming material according to claim 9.

12. The R is an alkyl group. A film-forming material according to claim 9 or claim 11.

13. The aforementioned R is one of the following selected from the group Me, Et, Pr, and Bu. A film-forming material according to claim 9 or claim 11.

14. The above R is Me The film-forming material according to claim 13.

15. The aforementioned material contains a reducing agent in addition to the aforementioned compound. A film-forming material according to claim 9 or claim 10.

16. The reducing agent is selected from ammonia and hydrogen. The film-forming material according to claim 15.

17. The reducing agent is ammonia and hydrogen. The film-forming material according to claim 15.

18. Co[tBu-NC(R)N-nPr] 2 A compound represented by (R is a hydrocarbon group). New compound.

19. The compound is a liquid (at 25°C (1 atm)). A novel compound according to claim 18.

20. The aforementioned R has 1 to 4 carbon atoms. A novel compound according to claim 18.

21. The R is an alkyl group. A novel compound according to claim 18 or claim 19.

22. The aforementioned R is one of the following selected from the group Me, Et, Pr, and Bu. A novel compound according to claim 18 or claim 19.

23. The above R is Me A novel compound according to claim 18 or claim 19.

Citation Information

Patent Citations

  • JP1974088159A

  • Perfect rolling mechanism of a finite stroke

    JP1977025957A

  • Film deposition method and storage medium

    JP2011063849A

  • Novel compounds and manufacturing methods

    JP7332211B2